The influence of incentives and motivation on teacher performance with supervision as an intervening variable at SMK PGRI Serang city - Guntur, Ahmad (Enrichment : Journal of Management, 2023)
Performance is a logical effect of a person which is caused by several factors, both internal and external, the only management strategy that is most effective for improving a teacher's work is giving him encouragement by providing incentives, and motivation is an effective way to improve teacher performance and supervision has a positive effect on teacher performance, the more supervised the teacher's performance will increase. To discuss and analyze improving teacher performance by providing incentives and motivation, identifying obstacles and barriers to teacher performance, as well as providing solutions and recommendations for teacher performance problems. In this research, no previous research has been found that discusses improving teacher performance with incentives, motivation and supervision at PGRI Vocational School, Serang City. The limitation of this research is only to analyze efforts to improve teacher performance with incentives and motivation as well as supervision as intervening variables at SMK PGRI Serang City. This research uses descriptive quantitative methods. There are 2 types of data sources used in this research, namely primary data and secondary data. The primary data used was a questionnaire sent to PGRI Vocational School teachers in Serang City. There were 95 samples from 211 total populations. The secondary data used is a document in the form of a 2022 teacher performance survey. Analysis was carried out with the help of SmartPLS software version 4. The research results explain that incentives and motivation as well as supervision have a positive and significant effect on teacher performance at PGRI Vocational School, Serang City.